Lipid-based nanoparticle delivery system approach for diabetic wounds: A review - Choerrunisa, Choerrunisa; Jafar, Garnadi; Sukmawati, Ika Kurnia (Institute of Computer Science (IOCS), 2025)
Diabetic wounds are a chronic complication that is difficult to heal due to impaired blood circulation, oxidative stress, and microbial infection. Conventional therapies are often ineffective due to poor drug penetration into damaged skin tissue and limited bioavailability of active compounds. Lipid nanoparticle-based drug delivery technology was developed to overcome these obstacles by increasing stability, skin penetration ability, and controlled drug release. Objective: This article aims to comprehensively review the role of lipid-based nanoparticle delivery systems in improving the effectiveness of diabetic wound healing therapy, including the mechanisms of absorption enhancement, active substance stability, and pharmacological activity. Methods: This study is a systematic literature review of national and international publications over the past ten years (2015–2025). Data sources were obtained from PubMed, ScienceDirect, and Google Scholar databases using keywords “lipid nanoparticles,” “diabetic wound healing,” and “transdermal drug delivery.” Inclusion criteria included experimental studies and review articles discussing lipid nanoparticle formulations and their therapeutic effects on diabetic wounds. Results: Various studies have shown that lipid-based nanoparticle systems, including nanostructured lipid carriers (NLCs) and solid lipid nanoparticles (SLNs), can improve the stability and permeation of active ingredients such as curcumin, asiatic acid, and other herbal extracts through the skin. This improvement contributes to better anti-inflammatory, antioxidant, and antibacterial activities, thereby accelerating the healing process of diabetic wounds. Conclusion: Lipid-based nanoparticle technology offers an innovative approach to diabetic wound therapy by improving the stability, bioavailability, and effectiveness of active ingredients. Further development is needed for formulation optimization and clinical validation to ensure the safety and effectiveness of its use in diabetic patients.